The Use of Titanium Mesh Cages in the Reconstruction of Anterior Column Defects in Active Spinal Infections: Can We Rest the Crest? - Sundararaj, Gabriel David (Korean Society of Spine Surgery, 2011)
STUDY DESIGN: Retrospective clinical series. PURPOSE: To assess whether titanium cages are an effective alternative to tricortical iliac crest bone graft for anterior column reconstruction in patients with active pyogenic and tuberculous spondylodiscitis. OVERVIEW OF LITERATURE: The use of metal cages for anterior column reconstruction in patients with active spinal infections, though described, is not without controversy. METHODS: Seventy patients with either tuberculous or pyogenic vertebral osteomyelitis underwent a single staged anterior debridement, reconstruction of the anterior column with titanium mesh cage and adjuvant posterior instrumentation. The lumbar spine was the predominant level of involvement. Medical co-morbidities were seen in 18 (25.7%) patients. A significant neurological deficit was seen in 32 (45.7%) patients. At follow up patients were assessed for healing of disease, bony fuson, and clinical outcome was assessed using Macnab's criteria. RESULTS: Final follow up was done on 64 (91.4%) patients at a mean average of 25 months (range, 12 to 110 months). Pathologic organisms could be identified in 42 (60%) patients. Forty two (60%) patients had histopathological findings consistent with tuberculosis. Thirty of 32 (93.7%) patients showed neurological recovery. The surgical wound healed uneventfully in 67 (95.7%) patients. Bony fusion was seen in 60 (93.7%) patients. At final follow up healing of infection was seen in all patients. As per Macnab's criteria 61 (95.3%) patients reported a good to excellent outcome. CONCLUSIONS: Inspite of the theoretical risks, titanium cages are a suitable alternative to autologous tricortical iliac crest bone graft in patients with active spinal infections.